Facile engineering and interfacing of styrenic block copolymers devices for low‐cost, multipurpose microfluidic applications - Hugo Salmon; M. Reza Rasouli; Nicholas Distasio; Maryam Tabrizian (Engineering Reports, 2021)
Abstract Soft thermoplastic elastomers (sTPE) and specifically styrenic block copolymers (SBC) are making rapid progress in the prototyping and mass production of microfluidic chips. However, these new materials lack guidelines and protocols for chips fabrication, curbing their widespread applications compared to polydimethylsiloxane. In this work, the prototyping potential of a commercially available SBC material, Flexdym, for continuous flow applications is explored. This SBC material exhibits both reversible and permanent self‐adhesion depending on the time and bonding temperature, allowing for rapid and adaptive chip fabrication. Replicates are embossed in 2 min, assembled and sealed in 10 min. Under continuous flow, stud interfaces fabricated with this method can withstand 1 bar with reversible bonding and up to 3 bar after permanent bonding. The integration of an acoustic transducer in an SBC chip to induce acoustic streaming enables rapid mixing and local enrichment of polystyrene microparticles up to 8× the injected concentration. The reversible bonding feature of SBC chips allows to culture endothelial cells in open channels and then close and perfuse through channel to stain the cell. Our finding suggests that TPE‐based materials offer numerous possibilities for prototyping microfluidic chips for analytical and biomedical applications when working with continuous flow at high pressure is required.